Negotiating Islamic Law and State Norms in Child Marriage Practices in Coastal Indonesia - Barkah, Qodariah; Sintang, Suraya; Morin, Leanne (Antmind Review: Journal of Sharia and Legal Ethics, 2025)
Despite national legal reforms aimed at curbing child marriage, the practice remains prevalent in Indonesia’s coastal Muslim communities. This study explores the socio-legal dynamics underpinning early marriage in South Minahasa, North Sulawesi, by examining the interaction between Islamic jurisprudence, customary norms, and formal state law. Using a qualitative socio-legal approach, data were collected through in-depth interviews with religious leaders, adat authorities, legal practitioners, affected families, court documents, and field observations. Findings reveal that dominant interpretations of classical Islamic law particularly the emphasis on biological maturity (baligh) as a prerequisite for marriage legitimize child marriage at the grassroots level, often reinforced by socio-economic pressures and honor-based cultural expectations. Moreover, legal instruments such as marriage dispensation and unregistered (siri) marriages are widely used to bypass formal legal constraints. This plural legal reality places religious courts in a normative dilemma between enforcing state law and accommodating communal values. The study argues that preventing child marriage requires not only statutory enforcement but also culturally sensitive engagement with religious authorities, community-based legal education, and a reinterpretation of Islamic norms through the lens of maqāṣid al-sharī‘ah (higher objectives of Islamic law). These findings contribute to broader global discussions on legal pluralism, human rights, and the role of faith-based norms in shaping family law and child protection policies.